Comparative Study of Cash Based and Non Cash Distributions in the Household Program (PKH) in Tekasire Village, Manggelewa District - Ega Saiful Subhan; Ery Tri Djatmika Rudijanto; Puji Handayati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Family Hope Program (PKH) is the country's poverty alleviation policy. In 2017 the Family Hope Program (PKH) has changed its distribution mechanism from cash distribution (cash based) to non-cash distribution. This change in the distribution mechanism is a form of the state's response to problems that arose earlier, so that through non-cash distribution, people are accustomed to accessing banking. This research is a descriptive qualitative research. Sources of data in this study are primary data and secondary data. Where the data collection using the technique of Observation, Interview, and Documentation. With the aim of the study to determine the comparison of the distribution of cash (cash based) and non-cash in the Family Hope Program (PKH) in Tekasire Village, Mnggelewa District. It is intended to be able to find out the shortcomings, advantages, similarities and differences in the distribution of the Family Hope Program Social Assistance (PKH). From the results of the study, it can be concluded that the comparison of Cash (cash based) and Non-Cash Disbursements in the Family Hope Program (PKH) in Tekasire Village, Manggelewa District found advantages and disadvantages, in Cash (cash based) the advantages are in the requirements that are easier, while in non-cash distributions, there are accuracy of targets, while the drawback in cash disbursement (cash based) is in the use of money and longer queues, while in non-cash distributions there are several shortcomings, one of which lies in bank procedures. In addition, there are also similarities and differences in cash-based and non-cash distributions, where the feeling is both assistance from the Ministry of Social Affairs and the difference lies in the instrument used in the form of receiving money directly while the non-cash used is an ATM card. So the Beneficiary Family (KPM) must first withdraw the money from the ATM card to get help.